Radio and television coverage of the miners' strike 1969-1970 - Westerståhl, Jörgen (University of Gothenburg, 1982)
On the request of the Board of the Swedish Broadcasting Corporation and the Labour Movement´s Archives, this survey was carried through of the news examination of the SBC and the treatment of the Swedish daily press of the conflict at LKAB. The purpose of the survey of the examination of the SBC was to ascertain its ´extent, attitude, matter-of-fact-ness and impartiality´.

On the request of the Board of the Swedish Broadcasting Corporation and the Labour Movement´s Archives, this survey was carried through of the news examination of the SBC and the treatment of the Swedish daily press of the conflict at LKAB. The purpose of the survey of the examination of the SBC was to ascertain its ´extent, attitude, matter-of-fact-ness and impartiality´.
Gruvstrejkens behandling i radio och TV 1969-1970
Keywords: internal politics; inrikespolitik; Media; Media; Social Sciences; Samhällsvetenskap